Managing Human Resources Management Policies in a Private Hospital and its Impact on Work-Life Balance and Employee Engagement - Luturlean, Bachruddin Saleh; Witjara, Edi; Prasetio, Arif Partono; Adhanissa, Salsa (JDM (Jurnal Dinamika Manajemen), 2020)
This study examines the role of human resources practice in enhancing work-life balance and engagement. We try to identify how are employees manage their work and life with the help of an organization to achieve stronger engagement. Data obtained by distributing a questionnaire to 200 employees from a private hospital in Banyuwangi. The collection of the questionnaire took 45 days and we have 113 useable responses. The technique used is mediation analysis using bootstrapping analysis. The results showed there is a positive effect of human resource practice on work-life balance. Both variables have a positive effect on employee engagement. Through the mediation analysis, it is known that work-life balance acts as mediation in the relationship between human resource practices and the level of employee involvement. Future studies can expand the participants from other hospitals in Banyuwangi or East Java.